2022
DOI: 10.7759/cureus.24025
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Two-Dimensional and Three-Dimensional Regional and Global Longitudinal Strain Echocardiography to Evaluate Complex Coronary Lesions in Patients With Non-ST-Segment Elevation Acute Coronary Syndrome

Abstract: Introduction A preliminary assessment of patients who suffer from severe and complex coronary artery lesions, such as three-vessel disease and/or a left main (LM) artery lesion, plays a critical contribution in determining prognosis and treatment plans for non-ST-segment elevation acute coronary syndrome (NSTE-ACS). Therefore, a pre-angiography (i.e., before angiography) predictor was required to cost-effectively evaluate severe and complex coronary lesions to efficiently direct our subsequent deali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This observation is in line with the findings of Raslan et al., which resonate with our results. Their study demonstrates a significant association between the complexity of coronary artery lesions in NSTE‐ACS patients, as determined by the SYNTAX score, and the absolute values of LV‐GLS% 12 …”
Section: Discussionmentioning
confidence: 93%
“…This observation is in line with the findings of Raslan et al., which resonate with our results. Their study demonstrates a significant association between the complexity of coronary artery lesions in NSTE‐ACS patients, as determined by the SYNTAX score, and the absolute values of LV‐GLS% 12 …”
Section: Discussionmentioning
confidence: 93%
“…The results showed significantly lower values of 2D GLS, 3D GLS, global circumferential strain, area strain, and global radial strain in the high score group compared to the low score group of patients. 37 Abdulrezak et al 38 found that there was a statistically significant positive correlation between the SYNTAX score and each of LVEDD and LVESD. On the other hand, a statistically significant negative correlation was observed between the SYNTAX score and GLS.…”
Section: Discussionmentioning
confidence: 99%